MAKTABGACHA TA`LIM MUASSASALARIDAGI KATTA GURUH TARBIYALANUVCHILARINING JISMONIY SIFATLARINI KUN TARTIBIDAGI JISMONIY TARBIYA SOG‘LOMLASHTIRISH ISHLARI ORQALI OSHIRISHNING SAMARALI YO‘LLARI - Radjapov, U.R.; Abdulazizova, M.A. (SCIENCE and SOCIETY, 2018)
The article contains the detailed information about the lessons in the open air at pre-school establishments in teaching children and forming in the relative stability to unfavorable influence of the environment (for example, rain, wind, warmth).
Keywords: morning gymnastics; physical train; muscule; temper; water treatment; feeling; physical minute; supporting activity; skin